Method for regenerating catalyst for alcohol production
Regenerating alcohol production catalysts with oxygen-containing gases in the gas phase restores their activity and selectivity, addressing the deterioration issue and ensuring stable alcohol production.
Patent Information
- Application Number
- JP2020208761
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-12-16
AI Technical Summary
The yield and selectivity of alcohol production using solid acid catalysts such as zeolites and heteropolyacids decrease over time due to catalyst deterioration, necessitating a method to regenerate and extend the catalyst's life for stable alcohol production.
Regenerate the deteriorated alcohol production catalysts by treating them with a regeneration gas containing oxygen gas, such as air, in the gas phase to restore activity and selectivity, using a catalyst supported on a silica carrier with heteropolyacids or their salts.
The method allows for the reuse of degraded catalysts, maintaining stable alcohol production over an extended period with improved ethylene conversion and ethanol selectivity.
Smart Images

Figure 0007615654000004 
Figure 0007615654000005 
Figure 0007615654000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for regenerating a catalyst for producing alcohol by the hydration reaction of an olefin. [Background technology]
[0002] Industrial ethanol is an important industrial chemical product that is widely used as an intermediate for organic solvents, organic synthesis raw materials, disinfectants, chemicals, etc. Industrial ethanol is known to be obtained by the hydration reaction of ethylene in the presence of liquid acids such as sulfuric acid and sulfonic acid, zeolite catalysts, metal oxide catalysts including tungsten, niobium, tantalum, etc., or solid acid catalysts in which heteropolyacids such as tungstophosphoric acid and tungstosilicic acid or phosphoric acid are supported on a silica carrier, a diatomaceous earth carrier, etc. In particular, a process using a solid catalyst in which phosphoric acid is supported on a carrier is industrially carried out. However, it has been reported that the yield or selectivity of alcohol gradually decreases with reaction time in catalysts such as zeolite and heteropolyacid, and the short catalyst life is a problem (Non-Patent Documents 1 and 2). Patent Documents 1 and 2 describe improved heteropolyacid catalysts, but sufficient life evaluation has not been performed, and these catalysts have not reached a level that can be used industrially. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 8-192047 [Patent Document 2] Japanese Patent Application Publication No. 8-225473 [Non-patent literature]
[0004] [Non-Patent Document 1] Industrial Chemistry Journal, Vol. 69, No. 10, 1966, pp. 32-32 [Non-Patent Document 2] Journal of the Petroleum Society, April 1963, pp. 336-341 Summary of the Invention [Problem to be solved by the invention]
[0005] When the yield of the target alcohol decreases, the reaction temperature is generally gradually increased in order to maintain the catalytic activity. However, the acid catalyst used as a catalyst for alcohol production is sensitive to heat, and if the reaction temperature is raised too high, the catalyst decomposes, resulting in rapid catalyst deterioration. In addition, the increase in reaction temperature reduces selectivity, leading to further catalyst deterioration. Therefore, from the viewpoint of extending the catalyst life and achieving a stable reaction over a long period of time, an effective method for regenerating the catalyst is strongly desired.
[0006] The present invention aims to provide a method for stably producing alcohol over a long period of time by making it possible to reuse a deteriorated alcohol production catalyst with reduced activity or alcohol selectivity in the production of alcohol by the hydration reaction of an olefin using a solid acid catalyst in which a heteropolyacid or a salt thereof is supported on a carrier. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted extensive research and have found that in the production of alcohols by olefin hydration in a gas phase, catalyst deterioration occurs due to reduction of heteropolyacid. Based on this finding, they have discovered that the activity and alcohol selectivity of a deteriorated catalyst can be restored by treating the deteriorated catalyst with a regeneration gas containing oxygen gas, thereby completing the present invention.
[0008] That is, the present invention relates to the following [1] to [7]. [1] A method for regenerating an alcohol production catalyst, the method comprising regenerating an alcohol production catalyst whose activity or alcohol selectivity has decreased, with a regeneration gas containing oxygen gas, the method being characterized in that the alcohol production catalyst is used for producing alcohol by supplying water and an olefin having 2 to 5 carbon atoms to a reactor and causing a hydration reaction in a gas phase, and the method being a solid acid catalyst in which a heteropolyacid or a salt thereof is supported on a carrier. [2] The method for regenerating a catalyst for alcohol production according to [1], wherein the regeneration gas is a mixed gas containing oxygen gas and an inert gas. [3] The method for regenerating a catalyst for alcohol production according to [1], wherein the regeneration gas is air. [4] The method for regenerating a catalyst for alcohol production according to any one of [1] to [3], wherein the temperature of the regeneration treatment is 20 to 350°C. [5] The method for regenerating a catalyst for alcohol production according to any one of [1] to [4], wherein the heteropolyacid is at least one compound selected from the group consisting of silicotungstic acid, phosphotungstic acid, phosphomolybdic acid, silicomolybdic acid, silicovanadotungstic acid, phosphovanadotungstic acid, and phosphovanadomolybdic acid. [6] The method for regenerating a catalyst for alcohol production according to any one of [1] to [5], wherein the support is silica. [7] The method for regenerating a catalyst for alcohol production according to any one of [1] to [6], wherein the olefin having 2 to 5 carbon atoms is ethylene, and the alcohol is ethanol. Effect of the Invention
[0009] According to the present invention, in the production of alcohol by the hydration reaction of an olefin using a solid acid catalyst in which a heteropolyacid or a salt thereof is supported on a carrier, it is possible to reuse a deteriorated alcohol production catalyst whose activity or alcohol selectivity has decreased, and it is possible to stably produce alcohol over a long period of time. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the change in ethylene conversion rate over time in Example 1 and Comparative Example 1. [Diagram 2] 1 is a graph showing the change over time in ethanol selectivity in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Preferred embodiments of the present invention will be described below, but it should be understood that the present invention is not limited to these embodiments and that various applications are possible within the spirit and scope of the present invention.
[0012] (Alcohol production catalyst) In one embodiment, a solid acid catalyst in which a heteropolyacid or a salt thereof (also referred to as a "heteropolyacid salt" in the present disclosure) is supported on a carrier is used as a catalyst for producing alcohol.
[0013] (Heteropolyacids, heteropolyacid salts) Heteropolyacids are composed of a central element and peripheral elements bonded with oxygen. The central element is usually silicon or phosphorus, but may be any one selected from a wide variety of elements in Groups 1 to 17 of the periodic table of elements. Specific examples include, but are not limited to, cupric ions; divalent beryllium, zinc, cobalt, or nickel ions; trivalent boron, aluminum, gallium, iron, cerium, arsenic, antimony, phosphorus, bismuth, chromium, or rhodium ions; tetravalent silicon, germanium, tin, titanium, zirconium, vanadium, sulfur, tellurium, manganese, nickel, platinum, thorium, hafnium, and cerium ions and other rare earth ions; pentavalent phosphorus, arsenic, vanadium, and antimony ions; hexavalent tellurium ions; and heptavalent iodine ions. Specific examples of peripheral elements include, but are not limited to, tungsten, molybdenum, vanadium, niobium, and tantalum.
[0014] Such heteropolyacids are also known as "polyoxoanions", "polyoxometalates" or "metal oxide clusters". Some well-known structures of anions are named after researchers in this field, such as the Keggin structure, the Wells-Dawson structure and the Anderson-Evans-Perloff structure. For details, see "Chemistry of Polyacids" (edited by the Chemical Society of Japan, Quarterly Chemistry Review No. 20, 1993). Heteropolyacids usually have a high molecular weight, for example, in the range of 700 to 8500, and include not only monomers but also dimeric complexes.
[0015] The heteropolyacid salt is not particularly limited as long as it is a metal salt or onium salt in which some or all of the hydrogen atoms of the heteropolyacid are substituted, and specific examples thereof include, but are not limited to, metal salts of lithium, sodium, potassium, cesium, magnesium, barium, copper, gold, and gallium, as well as onium salts of ammonia.
[0016] Heteropolyacids, especially when they are the free acids and some of their salts, have relatively high solubility in polar solvents such as water or other oxygenated solvents. Their solubility can be controlled by choosing the appropriate counter ion.
[0017] Examples of heteropolyacids that can be used as catalysts include Silicotungstic acid H4[SiW 12 O 40 ]·xH2O Phosphotungstic acid H3 [PW 12 O 40 ]·xH2O Phosphomolybdic acid H3 [PMo 12 O 40 ]·xH2O Silicomolybdic acid H4 [SiMo 12 O 40 ]·xH2O Tungsten carbide H 4+n [SiV n W 12-n O 40 ]·xH2O Phosphonatotungstic acid H 3+n [PV n W 12-n O 40 ]·xH2O Phosphovanadomolybdic Acid H 3+n [PV n Mo 12-n O 40 ]·xH2O Molybdocarbamic acid H 4+n [SiV n Mo 12-n O 40 ]·xH2O Silicomolybdotungstic acid H4 [SiMo n W 12-n O 40 ]·xH2O Phosphomolybdotungstic acid H3 [PMo n W 12-n O 40 ]·xH2O (In the formula, n is an integer of 1 to 11, and x is an integer of 1 or more.) These include, but are not limited to:
[0018] The heteropolyacid is preferably silicotungstic acid, phosphotungstic acid, phosphomolybdic acid, silicomolybdic acid, silicotungstic acid, silicovanadotungstic acid, phosphovanadotungstic acid, or phosphovanadomolybdic acid, and more preferably silicotungstic acid, phosphotungstic acid, silicovanadotungstic acid, or phosphovanadotungstic acid.
[0019] There is no particular limitation on the method for synthesizing such heteropolyacids, and any method may be used. For example, heteropolyacids can be obtained by heating an acidic aqueous solution (pH 1 to 2) containing a salt of molybdic acid or tungstic acid and a simple oxygen acid of a heteroatom or its salt. The heteropolyacid compound can be isolated, for example, by crystallizing and separating it as a metal salt from the heteropolyacid aqueous solution produced. Specific examples of the production of heteropolyacids are described on page 1413 of "New Experimental Chemistry Lectures 8: Synthesis of Inorganic Compounds (III)" (edited by the Chemical Society of Japan, published by Maruzen Co., Ltd., August 20, 1984, 3rd edition), but are not limited thereto. The structure of the synthesized heteropolyacid can be confirmed by chemical analysis as well as X-ray diffraction, UV, or IR measurement.
[0020] Preferred examples of the heteropolyacid salt include lithium salts, sodium salts, potassium salts, cesium salts, magnesium salts, barium salts, copper salts, gold salts, gallium salts, and ammonium salts of the above preferred heteropolyacids.
[0021] Specific examples of the heteropolyacid salt include lithium silicotungstic acid, sodium silicotungstic acid, cesium silicotungstic acid, copper silicotungstic acid, gold silicotungstic acid, and gallium silicotungstic acid; lithium phosphotungstic acid, sodium phosphotungstic acid, cesium phosphotungstic acid, copper silicotungstic acid, gold silicotungstic acid, and gallium silicotungstic acid; Lithium salt of molybdic acid, sodium salt of phosphomolybdic acid, caesium salt of phosphomolybdic acid, copper salt of phosphomolybdic acid, gold salt of phosphomolybdic acid, gallium salt of phosphomolybdic acid;Lithium salt of silicomolybdic acid, sodium salt of silicomolybdic acid, caesium salt of silicomolybdic acid, copper salt of silicomolybdic acid, gold salt of silicomolybdic acid, gallium salt of silicomolybdic acid;Lithium salt of silicomolybdic acid, sodium salt of silicomolybdic acid Thorium salts, caesium salts of phosphotungstic acid, copper salts of phosphotungstic acid, gold salts of phosphotungstic acid, gallium salts of phosphotungstic acid; lithium salts of phosphotungstic acid, sodium salts of phosphotungstic acid, caesium salts of phosphotungstic acid, copper salts of phosphotungstic acid, gold salts of phosphotungstic acid, gallium salts of phosphotungstic acid; lithium salts of phosphomolybdic acid salts, sodium salts of phosphovanadomolybdic acid, cesium salts of phosphovanadomolybdic acid, copper salts of phosphovanadomolybdic acid, gold salts of phosphovanadomolybdic acid, gallium salts of phosphovanadomolybdic acid; lithium salts of phosphovanadomolybdic acid, sodium salts of phosphovanadomolybdic acid, cesium salts of phosphovanadomolybdic acid, copper salts of phosphovanadomolybdic acid, gold salts of phosphovanadomolybdic acid, gallium salts of phosphovanadomolybdic acid, and the like.
[0022] Heteropolyacid salts include lithium silicotungstic acid, sodium silicotungstic acid, cesium silicotungstic acid, copper silicotungstic acid, gold silicotungstic acid, and gallium silicotungstic acid; lithium phosphotungstic acid, sodium phosphotungstic acid, cesium phosphotungstic acid, copper phosphotungstic acid, gold silicotungstic acid, and gallium phosphotungstic acid; lithium phosphomolybdic acid, sodium phosphomolybdic acid, cesium phosphomolybdic acid, copper phosphomolybdic acid, gold silicotungstic acid, and gallium phosphomolybdic acid; lithium silicic molybdic acid, sodium silicic molybdic acid, cesium silicic molybdic acid, copper silicic molybdic acid, gold silicic molybdic acid, and gallium silicic molybdic acid; Lithium salt of phosphotungstic acid, sodium salt of phosphotungstic acid, caesium salt of phosphotungstic acid, copper salt of phosphotungstic acid, gold salt of phosphotungstic acid, gallium salt of phosphotungstic acid; Lithium salt of phosphotungstic acid, sodium salt of phosphotungstic acid, caesium salt of phosphotungstic acid, copper salt of phosphotungstic acid, phosphotungstic acid
[0033] The preferred phosphovanadomolybdic acid is a gold salt, a gallium salt of phosphovanadotungstic acid, a lithium salt of phosphovanadomolybdic acid, a sodium salt of phosphovanadomolybdic acid, a cesium salt of phosphovanadomolybdic acid, a copper salt of phosphovanadomolybdic acid, a gold salt of phosphovanadomolybdic acid, a gallium salt of phosphovanadomolybdic acid, a lithium salt of phosphovanadomolybdic acid, or a sodium salt of phosphovanadomolybdic acid.
[0023] The heteropolyacid salts include lithium silicotungstic acid, sodium silicotungstic acid, cesium silicotungstic acid, copper silicotungstic acid, gold silicotungstic acid, and gallium silicotungstic acid; lithium phosphotungstic acid, sodium phosphotungstic acid, cesium phosphotungstic acid, copper silicotungstic acid, gold silicotungstic acid, and gallium silicotungstic acid; lithium silicotungstic acid, sodium silicotungstic acid, cesium silicotungstic acid, copper silicotungstic acid, gold silicotungstic acid, and gallium silicotungstic acid; More preferred are sodium salt of ivanadotungstic acid, cesium salt of silicotungstic acid, copper salt of silicotungstic acid, gold salt of silicotungstic acid, and gallium salt of silicotungstic acid; and lithium salt of phosphotungstic acid, sodium salt of phosphotungstic acid, cesium salt of phosphotungstic acid, copper salt of phosphotungstic acid, gold salt of phosphotungstic acid, and gallium salt of phosphotungstic acid.
[0024] It is particularly preferable to use a lithium salt of silicotungstic acid or a cesium salt of phosphotungstic acid as the heteropolyacid salt.
[0025] (Carrier) The heteropolyacid or heteropolyacid salt is used by being supported on a carrier, which is preferably at least one selected from the group consisting of silica, diatomaceous earth, titania, activated carbon, alumina, and silica-alumina, and more preferably silica.
[0026] (Silica carrier) Generally, synthetic amorphous silica is produced by either a dry method or a wet method. The combustion method, in which silicon tetrachloride is burned in a hydrogen flame in the presence of oxygen, is classified as a dry method, while the gel method, in which the neutralization reaction of sodium silicate and mineral acid is carried out in an acidic pH range to cause aggregation while suppressing the growth of primary particles, the sol-gel method, in which alkoxysilane is hydrolyzed, and the water glass method, in which sodium silicate is ion-exchanged to prepare active silicic acid, and then particles are grown in a seed particle-containing aqueous solution with a pH adjustment under heating, are classified as wet methods. Silica obtained by the combustion method is generally called fumed silica, silica obtained by the gel method is generally called silica gel, and silica obtained by dispersing silica particles obtained by the sol-gel method and the water glass method in a medium such as water is generally called colloidal silica.
[0027] In one embodiment, the silica carrier can be obtained by kneading fumed silica obtained by a combustion method, silica gel obtained by a gel method, and colloidal silica obtained by a sol-gel method or a water glass method, shaping the kneaded mixture, and then firing the shaped body.
[0028] When fumed silica, silica gel, and colloidal silica are mixed, molded, and fired, the size of the primary and secondary particles of the fired silica carrier and the internal state of the porous body change depending on the mixing ratio of each component, the mixing method, the firing conditions, etc., so the higher-order structure of the silica carrier cannot be specified. The formula of the silica carrier is SiO2.
[0029] There is no limitation on the fumed silica, and general fumed silica can be used. Examples of commercially available fumed silica include Aerosil (trademark) manufactured by Nippon Aerosil Co., Ltd., Reolosil (trademark) manufactured by Tokuyama Corporation, and CAB-O-SIL (trademark) manufactured by Cabot Corporation. Commercially available fumed silica is available in hydrophilic and hydrophobic grades, and either grade can be used. Representative fumed silica has physical properties such as a primary particle diameter of 7 to 40 nm and a specific surface area of 50 to 500 m. 2 / g, it is non-porous, has no internal surface area and is amorphous. It has a high purity as silicon oxide of 99% or more and contains almost no metals or heavy metals.
[0030] There is no limitation on the silica gel, and general silica gel can be used. Examples of commercially available silica gel include NIPGEL manufactured by Tosoh Silica Corporation, MIZUKASIL manufactured by Mizusawa Industrial Chemical Co., Ltd., CALiACT manufactured by Fuji Silysia Chemical Co., Ltd., and Sunsphere manufactured by AGC Si-Tech Co., Ltd. In general, silica gel is produced by using sodium silicate, which is a raw material obtained by dissolving sodium silicate glass (cullet) obtained by mixing and melting silica sand (SiO2) and soda ash (Na2CO3) in water, reacting sodium silicate with a mineral acid such as sulfuric acid under acidic conditions, and gelling the entire reaction solution by causing aggregation in a state in which the growth of primary particles is suppressed. The physical properties of silica gel are not particularly limited, but silica gel has characteristics such as small primary particles, high specific surface area, and hard secondary particles. Specific physical properties of silica gel include a BET specific surface area of 200 to 1000 m 2 / g, secondary particle diameter of 1 to 30 μm, and pore volume measured by nitrogen gas adsorption method (BJH method) of 0.3 to 2.5 mL / g. The higher the purity of the silica gel, the better, and the preferred purity is 95% by mass or more, and more preferably 98% by mass or more.
[0031] The colloidal silica is not particularly limited, and general colloidal silica can be used. Examples of commercially available colloidal silica include SNOWTEX (trademark) manufactured by Nissan Chemical Industries, Ltd., SILICADOL manufactured by Nippon Chemical Industry Co., Ltd., ADEKA Corporation's Adelite, CAB-O-SIL (trademark) TG-C colloidal silica manufactured by Cabot Corporation, and QUATRON (trademark) manufactured by Fuso Chemical Industry Co., Ltd. Colloidal silica is a dispersion of silica fine particles in a medium such as water. Methods for manufacturing colloidal silica include the water glass method and the sol-gel method using hydrolysis of alkoxysilane, and colloidal silica manufactured by either method can be used. Colloidal silica manufactured by the water glass method and colloidal silica manufactured by the sol-gel method may be used in combination. Representative physical properties of colloidal silica include a particle size of 4 to 80 nm and a solid content concentration of silica dispersed in water or an organic solvent of 5 to 40 mass%. The impurity concentration in colloidal silica is preferably low because it may affect the catalytically active components supported. The purity of silica in the solid content is preferably 99% by mass or more, and more preferably 99.5% by mass or more.
[0032] The silica carrier can be obtained by kneading fumed silica, silica gel, and colloidal silica, molding the resulting kneaded product, and then firing the molded product. Appropriate additives may be added during kneading. The blending ratio of fumed silica, silica gel, and colloidal silica is preferably 5 to 50 parts by mass of fumed silica, 40 to 90 parts by mass of silica gel, and 5 to 30 parts by mass of solid content of colloidal silica. More preferably, the blending ratio is 15 to 40 parts by mass of fumed silica, 45 to 70 parts by mass of silica gel, and 5 to 15 parts by mass of solid content of colloidal silica.
[0033] When mixing fumed silica, silica gel, and colloidal silica, water or additives can be added for the purpose of improving moldability, improving the strength of the final silica carrier, etc. The additives are not particularly limited, and additives used in the manufacture of general ceramic molded products can be used. Depending on the purpose, binders, plasticizers, dispersants, lubricants, wetting agents, antifoaming agents, etc. can be used.
[0034] Examples of binders include wax emulsion, gum arabic, lignin, dextrin, polyvinyl alcohol, polyethylene oxide, starch, methylcellulose, Na-carboxymethylcellulose, hydroxyethylcellulose, sodium alginate, ammonium alginate, gum tragacanth, etc. The viscosity of the kneaded material varies greatly depending on the type and concentration of the binder, so the type and amount of binder are selected to obtain a viscosity suitable for the molding method to be used.
[0035] Examples of the plasticizer include glycerin, polyethylene glycol, and dibutyl phthalate, and can increase the flexibility of the kneaded material.
[0036] Examples of dispersants for aqueous systems include carboxymethylcellulose ammonium (CMC-NH4), oligomers of acrylic acid or its ammonium salt, anionic surfactants, ammonium polycarboxylate, wax emulsion, various amines such as monoethylamine, pyridine, piperidine, tetramethylammonium hydroxide, etc., and examples of dispersants for non-aqueous systems include fatty acids, fatty acid esters, phosphate esters, synthetic surfactants, benzenesulfonic acid, etc. By adding these dispersants, it is possible to avoid the generation of aggregated particles and obtain a silica carrier having a uniform fine structure after firing.
[0037] Examples of the lubricant include hydrocarbon lubricants such as liquid paraffin, paraffin wax, and chlorinated hydrocarbons, and examples of the fatty acid lubricant include stearic acid, lauric acid, and metal salts thereof, fatty acid amides, etc. Addition of a lubricant reduces friction between powders, improves fluidity, and facilitates molding, and also makes it easier to remove the molded product from the mold.
[0038] A wetting agent can be added to improve the wetting properties of the powder and the dispersant. Examples of wetting agents include nonionic surfactants, alcohols, glycols, etc. for aqueous systems, and polyethylene glycol ethyl ether, polyoxyethylene ester, etc. for non-aqueous systems. These substances are easily adsorbed at the solid-liquid interface, and improve the wetting of solids by lowering the interfacial tension.
[0039] When handling a slurry-type kneaded product, a defoaming agent such as a nonionic surfactant, a polyalkylene glycol derivative, or a polyether derivative may be added.
[0040] These additives can be used alone or in combination with a number of additives at the same time, but it is desirable that they are effective when added in as small an amount as possible, are inexpensive, do not react with the powder, dissolve in water or a solvent, completely decompose in an oxidizing or non-oxidizing atmosphere at a relatively low temperature, for example below 400°C, leave no ash, especially alkali metals and heavy metals, after decomposition and explosion, produce non-toxic and non-corrosive decomposition gases, and do not interfere with the recycling of the fragments that were not made into products.
[0041] The shape of the silica carrier is not particularly limited. For example, it may be spherical, cylindrical, hollow cylindrical, plate-like, elliptical, sheet-like, honeycomb-like, etc. It is preferably spherical, cylindrical, hollow cylindrical, or elliptical, which facilitates filling into a reactor and supporting catalytically active components, and more preferably spherical or cylindrical.
[0042] The method of forming the silica carrier is not particularly limited. It is formed from a kneaded material containing fumed silica, silica gel, and colloidal silica by any convenient method such as mold molding, extrusion molding, rolling granulation, spray drying, etc. General mold molding involves putting the kneaded material into a metal mold, hitting it with a hammer or the like repeatedly to pack it well, and then pressing it with a piston and removing it from the mold, and is also called stamp molding. Extrusion molding generally involves packing the kneaded material into a press, extruding it from a die (mouthpiece), cutting it to an appropriate length, and molding it into a desired shape. Rolling granulation involves dropping the kneaded material onto a rotating disk placed at an angle, rolling the particles on the disk to grow them, and making them spherical. Spray drying generally involves spraying a thick slurry into hot air to obtain porous particles, although they do not become very large particles.
[0043] The size of the silica carrier is not particularly limited. It is desirable to take into consideration the handling during the production or loading of the catalyst carrying the catalytic active component, the pressure difference after loading into the reactor, and the reaction results of the catalytic reaction, since it affects the handling during the production or loading of the catalyst carrying the catalytic active component, the pressure difference after loading into the reactor, and the reaction results of the catalytic reaction. The size of the silica carrier is determined by the firing conditions, since the carrier shrinks during the firing of the molded body. When the silica carrier is spherical, the size of the silica carrier (after firing) is preferably 0.5 mm to 12 mm in diameter, more preferably 1 mm to 10 mm, and even more preferably 2 mm to 8 mm. When the silica carrier is not spherical, the size of the silica carrier (after firing) is preferably 0.5 mm to 12 mm in the dimension that is the maximum length when the size is measured, more preferably 1 mm to 10 mm, and even more preferably 2 mm to 8 mm. When the particle size of the silica carrier is 0.5 mm or more, it is possible to prevent a decrease in productivity during the production of the carrier and an increase in pressure loss when used as a catalyst. If the particle size of the silica carrier is 12 mm or less, it is possible to prevent a decrease in the reaction rate due to diffusion rate control within the carrier and an increase in by-products.
[0044] Before or after calcination, if necessary, treatment with Marmerizer (registered trademark) (Fuji Paudal Co., Ltd.) or the like can be performed to adjust the shape of the silica carrier. For example, a cylindrical molded body before calcination can be molded into a spherical shape by treating it with the Marmerizer (registered trademark).
[0045] The calcination method is not particularly limited, but there is an appropriate calcination temperature range from the viewpoint of decomposing the additives and preventing the destruction of the silica structure. The calcination temperature is preferably 300°C to 1000°C, more preferably 500°C to 900°C. When the calcination temperature is in this range, the additives are completely decomposed and the performance of the silica carrier is not adversely affected. In addition, the specific surface area of the silica carrier is also improved. The calcination treatment can be carried out under either oxidizing or non-oxidizing conditions. For example, the calcination treatment may be carried out in an air atmosphere or in an inert gas atmosphere such as nitrogen gas. There is also no particular limit to the time of the calcination treatment, and it can be appropriately determined depending on the shape and size of the molded body, the type and amount of the additives used, etc.
[0046] In one embodiment, the silica carrier has mesopores with a pore size of 2 to 50 nm and macropores with a pore size of more than 50 nm and 1000 nm or less in a pore size distribution measurement. The presence of mesopores can be confirmed by a gas adsorption method (BJH method). The presence of macropores can be confirmed by a mercury intrusion method. In general, mercury intrusion and gas adsorption methods (BJH method) are widely used for measuring the pore size distribution of porous substances such as silica. In terms of the classification of pores by the IUPAC (International Union of Pure and Applied Chemistry), the mercury intrusion method can measure macropores of 50 nm or more and some mesopores of 2 nm to less than 50 nm, while the gas adsorption method can measure mesopores and micropores of 2 nm or less. When the silica carrier has macropores of the above sizes, the diffusion rate of substances in the pores is further improved. When such a silica carrier is used as a catalyst, it is expected that the activity will be improved by increasing the main reaction rate, and that the selectivity will be improved by suppressing the successive side reactions of the target product. By having mesopores of the above size in addition to macropores, the supported components can be highly dispersed, and the catalytic activity can be improved by increasing the number of reaction active sites.
[0047] In the silica carrier, the distribution ratio of each pore is not particularly limited, and an appropriate pore size distribution ratio can be selected depending on the type of reaction using the silica carrier. The pore size distribution ratio can be adjusted by the mixing ratio of fumed silica, silica gel, and colloidal silica when producing the silica carrier, the type and amount of additives used, the firing temperature, the molding method, etc.
[0048] In the pore size distribution by mercury intrusion porosimetry, the pore volume of the macropores of the silica carrier (integral value of the total macropore volume) is preferably 0.05 to 0.50 cc / g. The pore volume of the macropores of the silica carrier is more preferably 0.07 to 0.40 cc / g, and further preferably 0.10 to 0.30 cc / g. When the pore volume of the macropores of the silica carrier is in the range of 0.05 to 0.50 cc / g, both the diffusion rate of the substance and the strength of the carrier can be achieved.
[0049] The specific surface area of the silica support measured by the BET method (BET specific surface area) is 200 to 500 m2 The BET specific surface area of the silica carrier is preferably 220 to 400 m 2 / g, and more preferably 240 to 400m 2 / g. The BET specific surface area of the silica support is 200 to 500 m 2 When the amount of the carboxyl group is in the range of 1 / g, a sufficient reaction rate can be obtained when the carboxyl group is catalyzed.
[0050] The bulk density of the silica carrier is preferably 300 to 700 g / L. The bulk density of the silica carrier is more preferably 400 to 650 g / L, and further preferably 450 to 600 g / L. When the bulk density of the silica carrier is in the range of 300 to 700 g / L, the required amount of active ingredient can be supported and the strength of the carrier can be maintained.
[0051] The average pore size of the mesopores in the silica carrier measured by the gas adsorption method (BJH method) is preferably 3 to 16 nm. The average pore size of the mesopores in the silica carrier measured by the gas adsorption method (BJH method) is more preferably 4 to 14 nm, and further preferably 5 to 12 nm. When the average pore size of the mesopores in the silica carrier measured by the gas adsorption method (BJH method) is in the range of 3 to 16 nm, the specific surface area measured by the BET method is sufficient.
[0052] The carrier may have any shape, and there is no particular limitation to the shape. The carrier may be, for example, powder, sphere, pellet, etc., and is preferably spherical or pellet. There is no particular limitation to the particle size of the carrier. The particle size of the carrier varies depending on the reaction form, but when used in a fixed bed system, it is preferably 2 mm to 10 mm, and more preferably 3 mm to 7 mm.
[0053] There is no particular limitation on the method for supporting the heteropolyacid or a salt thereof on the carrier, but in general, the heteropolyacid or a salt thereof is dissolved or suspended in a solvent, the resulting solution or suspension is absorbed into the carrier, and the solvent is then evaporated.
[0054] The method of supporting the heteropolyacid salt on the carrier includes, but is not limited to, a method of supporting the heteropolyacid on the carrier and then supporting the raw material of the element that forms the salt, a method of supporting the heteropolyacid and the raw material of the element that forms the salt together on the carrier, a method of supporting a heteropolyacid salt prepared in advance on the carrier, and a method of supporting the raw material of the element that forms the salt on the carrier and then supporting the heteropolyacid. In any of the above methods, the heteropolyacid, its salt, and the raw material of the element that forms the salt can be supported on the carrier by dissolving or suspending them in a suitable solvent. The solvent may be any solvent that can dissolve or suspend the heteropolyacid, its salt, or the raw material of the element that forms the salt, and water, an organic solvent, or a mixture thereof, etc., are used, and preferably water, an alcohol, or a mixture thereof is used.
[0055] Specifically, the amount of heteropolyacid or its salt supported on the carrier can be adjusted by dissolving the heteropolyacid or its salt in distilled water or the like in an amount equivalent to the amount of water absorbed by the carrier, and impregnating the carrier with the solution. In another embodiment, the amount of heteropolyacid or its salt supported on the carrier can also be adjusted by immersing the carrier in a solution of an excess amount of heteropolyacid or its salt while moving it moderately, and then filtering to remove the excess heteropolyacid or its salt. The volume of the solution or suspension varies depending on the carrier used, the supporting method, etc. The carrier impregnated with the heteropolyacid or its salt is placed in a heating oven for several hours to evaporate the solvent, thereby obtaining a solid acid catalyst supported on the carrier. There is no particular limitation on the drying method, and various methods such as a stationary type and a belt conveyor type can be used. In addition, the amount of heteropolyacid or its salt supported on the carrier can be accurately measured by chemical analysis such as ICP and XRF.
[0056] The amount of the heteropolyacid or a salt thereof supported on the carrier is preferably 10 to 150 parts by mass, and more preferably 30 to 100 parts by mass, in terms of the total mass of the heteropolyacid or a salt thereof per 100 parts by mass of the carrier.
[0057] (Production of alcohol by hydration of olefin) The alcohol can be obtained by supplying water and an olefin having 2 to 5 carbon atoms to a reactor using a solid acid catalyst in which a heteropolyacid or a heteropolyacid salt is supported on a carrier (hereinafter referred to as an "alcohol production catalyst"), and carrying out a hydration reaction in the gas phase.
[0058] A specific example of an alcohol production reaction by hydration of an olefin having 2 to 5 carbon atoms is shown in formula (1). [ka] (In the formula, R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; R 1 ~R 4 The total number of carbon atoms is 0 to 3.
[0059] The olefin having 2 to 5 carbon atoms that can be used in the hydration reaction of the olefin using the catalyst for producing alcohol is not particularly limited. As the olefin having 2 to 5 carbon atoms, ethylene, propylene, n-butene, isobutene, pentene, or a mixture of two or more of them can be preferably mentioned, and ethylene is more preferable. Although there is no limitation on the ratio of the olefin to water used, since the reaction rate is highly dependent on the concentration of the olefin and the energy cost of the alcohol production process increases when the water concentration is high, the molar ratio of the olefin to water is preferably water:olefin=0.01 to 2.0, and more preferably water:olefin=0.1 to 1.0.
[0060] There is no limitation on the type of olefin hydration reaction using the catalyst for alcohol production, and any reaction type can be used. Preferred types include a fixed bed type, a fluidized bed type, and a suspended bed type from the viewpoints of ease of separation from the catalyst and reaction efficiency, and a fixed bed type that requires the least energy for separation from the catalyst is more preferred.
[0061] When a fixed bed system is used, the gas space velocity is not particularly limited, but from the viewpoint of energy and reaction efficiency, it is preferably 500 to 15000 / hr, more preferably 1000 to 10000 / hr. If the gas space velocity is 500 / hr or more, the amount of catalyst used can be effectively reduced, and if it is 15000 / hr or less, the amount of gas circulated can be reduced, so that within the above range, alcohol production can be performed more efficiently.
[0062] There is no restriction on the reaction pressure in the olefin hydration reaction using the catalyst for alcohol production. Since the olefin hydration reaction is a reaction in which the number of molecules is reduced, it is generally advantageous to carry out the reaction at high pressure. The reaction pressure is preferably 0.5 to 7.0 MPaG, more preferably 1.5 to 4.0 MPaG. "G" means gauge pressure. If the reaction pressure is 0.5 MPaG or more, a sufficient reaction rate can be obtained, and if the reaction pressure is 7.0 MPaG or less, the costs of installing equipment related to condensation measures and evaporation of olefins, equipment related to high-pressure gas safety measures, and energy can be further reduced.
[0063] The reaction temperature of the olefin hydration reaction using the catalyst for alcohol production is not particularly limited and can be carried out at a wide range of temperatures. Taking into consideration the thermal stability of the heteropolyacid or heteropolyacid salt and the temperature at which water, one of the raw materials, does not condense, the reaction temperature is preferably 100 to 550°C, more preferably 150 to 350°C.
[0064] The hydration reaction of olefins using a catalyst for alcohol production is an equilibrium reaction, and the conversion rate of olefins is at most the equilibrium conversion rate. For example, the equilibrium conversion rate in the production of ethanol by hydration of ethylene is calculated to be 7.5% at a temperature of 200°C and a pressure of 2.0 MPaG. Therefore, in the process for producing alcohol by hydration of olefins, the maximum conversion rate is determined by the equilibrium conversion rate, and as seen in the example of ethylene, the equilibrium conversion rate of the hydration reaction of olefins tends to be small, so industrially, there is a strong demand for carrying out the hydration reaction of olefins with high efficiency under mild conditions.
[0065] In the hydration reaction of olefins using a catalyst for alcohol production, the loss of olefins can be reduced by recycling unreacted olefins to the reactor. There is no limitation on the method of recycling unreacted olefins to the reactor, and olefins may be isolated from the process fluid discharged from the reactor and recycled, or may be recycled together with other inert components. Usually, industrial grade ethylene often contains a very small amount of ethane. Therefore, when using ethylene containing ethane and recycling unreacted ethylene to the reactor, it is desirable to purge a part of the recovered ethylene gas outside the system to prevent ethane from concentrating and accumulating.
[0066] In the hydration reaction of olefins using a catalyst for alcohol production, the produced alcohol may be dehydrated, and an ether compound may be produced as a by-product. For example, when ethanol is obtained by hydration of ethylene, diethyl ether is produced as a by-product. This diethyl ether is thought to be produced by a dehydration reaction from two molecules of ethanol, and when ethanol is produced by hydration of ethylene, the reaction yield is significantly reduced. However, by recycling the by-product diethyl ether to the reactor, diethyl ether is converted to ethanol, and ethanol can be produced from ethylene with extremely high efficiency. There are no particular limitations on the method of recycling the by-product ether compound to the reactor, but there are, for example, a method of isolating the ether compound from the component distilled from the reactor and recycling it to the reactor, and a method of recycling it to the reactor as a gas component together with unreacted olefin.
[0067] (Catalyst regeneration treatment) The present inventors have found that a catalyst deteriorated by the production of alcohol, specifically a catalyst with reduced activity or alcohol selectivity, can be treated with a regeneration gas containing oxygen gas to oxidize the heteropolyacid reduced during the reaction and regenerate the catalyst. It is presumed that the activity or alcohol selectivity of a heteropolyacid decreases because its acidity decreases when it is reduced. There is no particular limitation on the regeneration gas used to regenerate the catalyst as long as it contains oxygen gas. The regeneration gas may be a mixed gas of oxygen gas and an inert gas such as nitrogen gas. Examples of the inert gas include nitrogen gas and noble gases such as helium and argon, and nitrogen gas is preferred from the viewpoint of cost. It is more preferable to use air as the regeneration gas, which is a mixed gas of oxygen gas and an inert gas. There is no particular limitation on the treatment of the catalyst using the regeneration gas, and any known method can be used. For example, the catalyst may be treated in the reactor by stopping the introduction of the raw materials such as olefins and water without removing the catalyst from the reactor, and then completely desorbing the olefins, alcohols, etc. adsorbed on the catalyst by passing an inert gas through the reactor. Alternatively, the reaction may be stopped by stopping the introduction of the raw materials such as olefins and water, and after sufficiently cooling the catalyst layer, the catalyst may be extracted from the reactor and filled in another container, and the catalyst may be regenerated in the other container. From the viewpoint of the labor of refilling the catalyst and the cost of the container for regeneration, it is preferable to perform the regeneration treatment in the reactor without removing the catalyst from the reactor, which shortens the reaction stop time and makes it possible to perform the regeneration treatment economically advantageously.
[0068] The pressure of the regeneration gas may be normal pressure or pressurized, and is not particularly limited. When the regeneration gas is pressurized, a higher oxygen partial pressure can be obtained, so that the catalyst can be regenerated more effectively. The pressure of the regeneration gas is preferably -0.5 to 4 MPaG, more preferably 0 to 2 MPaG.
[0069] The oxygen concentration in the regeneration gas is not particularly limited, but is preferably 10 to 50 mol %. The higher the oxygen concentration, the higher the oxygen partial pressure that can be obtained, and therefore the more effectively the catalyst can be regenerated.
[0070] The regeneration treatment time is preferably 1 to 100 hours, more preferably 3 to 30 hours.
[0071] The regeneration temperature is preferably 20 to 350° C., and more preferably 100 to 250° C. The higher the regeneration temperature, the more effectively the catalyst can be regenerated. On the other hand, by setting the regeneration temperature to 350° C. or less, the energy cost associated with the regeneration process can be reduced. EXAMPLES
[0072] The present invention will be further described with reference to the following examples and comparative examples. However, these examples are merely illustrative of the present invention and are not intended to limit the present invention.
[0073] 1. Preparation of silica support 40 parts by mass of Aerosil (trademark) 300 (manufactured by Nippon Aerosil Co., Ltd.) as fumed silica, 60 parts by mass of CALiACT G6 (manufactured by Fuji Silysia Chemical Co., Ltd.) as silica gel, and 40 parts by mass of Snowtex O (manufactured by Nissan Chemical Co., Ltd.) as colloidal silica were kneaded in a kneader, and then water and additives (methylcellulose: SM-4000 manufactured by Shin-Etsu Chemical Co., Ltd., resin binder: Serander (registered trademark) YB-132A manufactured by Yuken Kogyo Co., Ltd.) were added to the kneader in appropriate amounts and further kneaded to prepare a kneaded product. Next, the kneaded product was put into an extrusion molding machine equipped with a die having a 3 mmφ circular hole at its tip. The intermediate extruded from the extrusion molding machine was cut with a cutter to 3 mm to obtain a cylindrical pre-fired molded body. The pre-calcined molded body was formed into a spherical shape using a Marumerizer (registered trademark), pre-dried at 70° C., and then calcined at a temperature of 820° C. in an air atmosphere to obtain a silica carrier A.
[0074] The water absorption rate of the carrier refers to a value measured by the following measurement method. (1) Weigh approximately 5 g of carrier using a balance (W1g) and place in a 100 mL beaker. (2) Add approximately 15 mL of pure water (ion-exchanged water) to the beaker so that the carrier is completely covered. (3) Leave it for 30 minutes. (4) Pour the carrier and pure water onto a wire mesh and drain the pure water. (5) Remove any water adhering to the surface of the carrier by gently pressing it with a paper towel until the surface becomes matte. (6) Measure the weight of the carrier + pure water (W2g). (7) Calculate the water absorption rate of the carrier using the following formula. Water absorption rate (g / g-carrier) = (W2-W1) / W1 Therefore, the water absorption amount (g) of the carrier is calculated by multiplying the water absorption rate (g / g) of the carrier by the mass (g) of the carrier used.
[0075] 2. Preparation of catalyst for alcohol production using tungstosilicic acid supported on silica support Commercially available Keggin-type tungstosilicic acid 26-hydrate (H4SiW 12 O 40 150 g of silica carrier A (26H2O; manufactured by Nippon Inorganic Chemical Industry Co., Ltd.) was weighed and placed in an eggplant flask, and distilled water was added to a volume equivalent to 95% of the water absorption of the silica carrier A to dissolve the silicotungstic acid. Next, 300 mL of the silica carrier A was weighed and placed in the eggplant flask containing the solution of silicotungstic acid. After addition, the eggplant flask was stirred so that the liquid would come into contact with the silica carrier A, and the silicotungstic acid was supported on the silica carrier A. The silica carrier A supporting the silicotungstic acid was removed from the eggplant flask, spread on a tray, and air-dried for 1 hour. Next, the air-dried silica carrier supporting the silicotungstic acid was placed in a dryer while still on the tray, and dried for 5 hours under conditions of 130°C, and then removed from the dryer, transferred into a dried desiccator, and cooled to room temperature to obtain a catalyst A for alcohol production in which the silicotungstic acid was supported on the silica carrier A.
[0076] 3. Hydration of ethylene (gas recycling evaluation) After the catalyst A for alcohol production was filled into a SUS vertical gas-phase fixed-bed reactor, the temperature and pressure were controlled, and vaporized water from an evaporator and a predetermined amount of ethylene from a mass flow controller were introduced into the reactor. The reaction gas after passing through the reactor was cooled, and the condensed liquid and the reaction gas from which the condensate had been removed were sampled for a certain period of time. A portion of the reaction gas from which the condensate had been removed was purged to prevent the accumulation of inert gases such as ethane, and the remaining gas was introduced into a compressor as a recycled gas, where it was pressurized and recycled to the reactor. The sampled liquid (reaction liquid) and reaction gas were analyzed using a gas chromatograph and a Karl Fischer analyzer, and the reaction results were calculated.
[0077] 4.Analysis of reaction gases The sampled reaction gas was analyzed using a gas chromatography apparatus (apparatus name: 7890) manufactured by Agilent Technologies, Inc., with a system program using multiple columns and two detectors. Gas chromatography conditions Oven: Hold at 40°C for 3 minutes, then increase temperature to 200°C at 20°C / min. Carrier gas: Helium Split ratio: 10:1 Column used (Agilent Technologies, Inc.) HP-1(2m)+GasPro(30m)32m×320μm×0μm DB-624 60m x 320μm x 1.8μm Detector Front detector: FID (heater 230℃, hydrogen flow rate 40mL / min, air flow rate 400L / min) Back detector: FID (heater 230℃, hydrogen flow rate 40mL / min, air flow rate 400L / min) Auxiliary detector: TCD (heater 230℃, reference flow rate 45mL / min, makeup flow rate 2mL / min)
[0078] 5. Analysis of the reaction mixture The sampled reaction solution was analyzed using a gas chromatography device (device name: 6850) manufactured by Agilent Technologies, Inc. The water concentration in the reaction solution was analyzed using a Karl Fischer analyzer manufactured by Mitsubishi Chemical Corporation. Column used: PoraBONDQ 25m x 0.53mmID x 10μm Oven temperature: 100°C for 2 minutes, then increase to 240°C at 5°C / min. Injection temperature: 250℃ Detector temperature: 300℃
[0079] The ethylene conversion, ethanol selectivity, and acetaldehyde selectivity were calculated by the following formulas. Ethylene conversion rate (mol%) = (moles of reacted ethylene / moles of fed ethylene) x 100 Ethanol selectivity (mol%) = (moles of ethanol produced / moles of ethylene fed) x 100 Acetaldehyde selectivity (mol%)=(moles of acetaldehyde produced / moles of ethylene fed)×100
[0080] 6. Catalyst regeneration The supply of the raw material gas was stopped, and the reactor was purged with nitrogen gas instead, and then a predetermined amount of air was introduced into the reactor from a mass flow controller. At this time, the catalyst was regenerated at a pressure of 0.0 MPaG and a temperature of 130°C.
[0081] <Example 1> 300 mL of the catalyst A for alcohol production was weighed out and packed into a tubular reactor (made of SUS316, inner diameter 34 mm, length 1500 mm), and the pressure was increased to 2.0 MPaG after replacing with nitrogen gas. Next, the reactor was heated to 190°C, and when the temperature stabilized, water and ethylene were fed into the reactor in amounts such that the GHSV (gas space velocity) was 3000 / hr and the molar ratio of water to ethylene was 0.3, and ethanol was produced by the hydration reaction of ethylene. After feeding water and ethylene, the temperature was stabilized, and the heat source temperature of the reactor was adjusted so that the temperature of the catalyst layer was 194°C. Since the acetaldehyde selectivity increased to 0.22% at 4100 hours after the start of the hydration reaction, the supply of the raw material was stopped, and the reactor was purged for 3 hours using nitrogen gas at a flow rate of GHSV (gas space velocity) 3000 / hr. After that, the heat source temperature of the reactor was adjusted so that the temperature of the catalyst layer was 130°C. Air gas was introduced into the reactor at normal pressure with a GHSV of 1000 / hr, and regeneration treatment was carried out for 12 hours. After the regeneration treatment, the reaction was restarted, and the acetaldehyde selectivity dropped to 0.12%. After 5000 hours had elapsed since the start of the hydration reaction, the ethylene conversion rate was 3.99%, and the ethanol selectivity was 99.4%. The results are shown in Table 1.
[0082] <Comparative Example 1> The hydration reaction was continued without regeneration treatment using the same catalyst and reaction conditions as those used in Example 1. The results are shown in Table 2. 5000 hours after the start of the hydration reaction, the ethylene conversion rate decreased to 3.80%, the ethanol selectivity decreased to 98.9%, and the acetaldehyde selectivity increased to 0.44%. The results are shown in Table 2.
[0083] The changes in ethylene conversion rate over time in Example 1 and Comparative Example 1 are shown in graphs in FIG. 1 and in ethanol selectivity over time in FIG.
[0084] From the above results, it is clear that by performing a catalyst regeneration treatment, the ethylene conversion rate and ethanol selectivity can be maintained even when the reaction is carried out for a long period of time.
[0085] Since the ethylene conversion rate is low in commercial ethanol plants, a difference of 0.2% in conversion rate has a large effect on productivity and costs. If the annual production volume is assumed to be 50,000 tons, a conversion rate of 0.2% is equivalent to approximately 2,400 tons. Assuming the price of anhydrous ethanol is 120 yen / kg, the cost benefit of catalyst regeneration is roughly estimated at 300 million yen per year.
[0086] [Table 1]
[0087] [Table 2] [Industrial Applicability]
[0088] According to the present invention, it becomes possible to reuse a deteriorated catalyst for alcohol production whose activity or alcohol selectivity has decreased, and alcohol can be stably produced for a long period of time.
Claims
1. A method for regenerating a catalyst for alcohol production, the method comprising the steps of: regenerating a catalyst for alcohol production whose activity or alcohol selectivity has decreased, with a regeneration gas containing oxygen gas; the catalyst for alcohol production is used for producing alcohol by supplying water and an olefin having 2 to 5 carbon atoms to a reactor and causing a hydration reaction in a gas phase; the catalyst is a solid acid catalyst in which a heteropolyacid or a salt thereof is supported on a carrier; and the temperature of the regeneration treatment is 20 to 130°C.
2. 2. The method for regenerating a catalyst for alcohol production according to claim 1, wherein the regeneration gas is a mixed gas containing oxygen gas and an inert gas.
3. 2. The method for regenerating a catalyst for alcohol production according to claim 1, wherein the regeneration gas is air.
4. The method for regenerating a catalyst for alcohol production according to any one of claims 1 to 3, wherein the heteropolyacid is at least one compound selected from the group consisting of silicotungstic acid, phosphotungstic acid, phosphomolybdic acid, silicomolybdic acid, silicovanadotungstic acid, phosphovanadotungstic acid, and phosphovanadomolybdic acid.
5. 5. The method for regenerating a catalyst for alcohol production according to claim 1, wherein the support is silica.
6. The method for regenerating a catalyst for alcohol production according to any one of claims 1 to 5, wherein the olefin having 2 to 5 carbon atoms is ethylene, and the alcohol is ethanol.
Citation Information
Patent Citations
Regeneration of catalyst for dehydrooxidation of isobutric acid
JP1988042738A
Method and catalyst for hydration of olefin
JP1996192047A
Method of hydrating olefin
JP1996225473A
Method for regenerating lower aliphatic carboxylic acid ester production catalyst, method for producing lower carboxylic acid ester production catalyst thereby, lower aliphatic acid ester production catalyst regenerated by the regeneration method, and method for producing lower aliphatic acid ester by using the catalyst
JP2003071299A
Method for producing alcohol and catalyst for producing alcohol
WO2020090756A1